Why Plato wrote - Allen, Danielle S., 1971- (Malden, MA : Wiley-Blackwell, 2010)
'Why Plato Wrote is the first book to be published in the prestigious Blackwell Bristol Lecture Series in Greece, Rome and the Classical Tradition. In this thought-provoking text Danielle Allen eloquently argues that Plato wrote to change Athenian culture and thereby transform Athenian politics. She makes the case that Plato was not only the world's first systematic political philosopher, but also the western world's first think-tank activist and message man. Allen contends that the roles of philosopher and message man were not mutually exclusive, and that Plato's pursuit of language as a vehicle for affecting cultural norms was grounded in his philosophy of language. Why Plato Wrote is a lucid and engaging commentary on Plato's philosophy of language and its relation to his political theory'--
Machine generated contents note: Preface: Why think about Plato? -- Part I: Why Plato Wrote. -- Chapter 1: Who Was Plato? -- Chapter 2: The Importance of Symbols to Human Life. -- Chapter 3: The Philosopher as Model-Maker. -- Chapter 4: The Philosopher as Shadow-Maker. -- Chapter 5: What Plato Wrote. -- Chapter 6: How Plato Lived. -- Part II: What Plato Did. -- Chapter 7: The Case for Influence. -- Chapter 8: Culture War Emergent. -- Chapter 9: Culture War Concluded. -- Epilogue: And to my colleagues.
Includes bibliographical references and index.
Keywords: Plato; Authorship -- Psychological aspects